Family Financial Resilience Strategy: Analysis of the Effect of Emergency Fund on Financial Welfare in Sentul Village, Batang Regency (International Forum of Researchers and Lecturers, 2025)
This study investigates the influence of emergency funds on the financial well-being of families in Sentul Village, Gringsing District, Batang Regency, while exploring the moderating roles of digital financial literacy, investment behavior, and financial adaptability. Drawing from a narrative literature review, the research emphasizes that digital financial literacy significantly enhances financial resilience, despite rural limitations in infrastructure and access to formal education. The investment behavior score reveals nuanced relationships with financial conditions, showing that villagers often rely on traditional physical assets as a contextual strategy for managing financial risk. The financial well-being index reflects a multifaceted construct shaped by both objective economic indicators and socio-psychological dimensions. Importantly, financial adaptation behavior emerges as a strong moderating factor, helping families maintain stability and well-being amid economic fluctuations. The study makes a theoretical contribution by integrating Financial Behavior Theory with the financial well-being framework within the rural Indonesian setting, offering a more comprehensive understanding of how rural households cope with financial challenges. In terms of practical application, the research suggests the development of digital financial literacy programs tailored to local culture, the design of hybrid financial products that combine traditional practices with modern tools, and the integration of emergency fund systems that align with local economic realities. Moreover, the study advocates for a collaborative approach involving communities, local institutions, and policymakers to build a sustainable financial resilience ecosystem for rural families. By focusing on the interplay between digital knowledge, behavioral adaptability, and contextual financial practices, this research provides insights into strengthening the financial foundations of rural households in a way that is both inclusive and responsive to their unique socio-economic environments.